Fouling cake layer in a submerged anaerobic membrane bioreactor treating saline wastewaters: curse or a blessing? - Stuckey, David C.; Vyrides, Ioannis (My University, 2011)
The treatment of inhibitory (saline) wastewaters is known to produce considerable amounts of soluble microbial products (SMPs), and this has been implicated in membrane fouling; the fate of these SMPs was of considerable interest in this work. This study also investigated the contribution of SMPs to membrane fouling of the; (a) cake layer/biofilm layer, (b) the compounds below the biofilm/ cake layer and strongly attached to the surface of the membrane, (c) the compounds in the inner pores of the membrane, and (d) the membrane. It was found that the cake/biofilm layer was the main reason for fouling of the membrane. Interestingly, the bacteria attached to the cake/biofilm layer showed higher biodegradation rates compared with the bacteria in suspension. Moreover, the bacteria attached to the cake layer showed higher amounts of attached extracellular polysaccharides (EPS) compared with the bacteria in suspension, possibly due to accumulation of the released EPS from suspended biomass in the cake/biofilm layer. Molecular weight (MW) analysis of the effluent and reactor bulk showed that the cake layer can retain a large fraction of the SMPs in the reactor and prevent them from being released into the effluent. Hence, while cake layers lead to lower fluxes in submerged anaerobic membrane bioreactors (SAMBRs), and hence higher costs, they can improve the quality of the reactor effluent.
Keywords: Fouling; Cake layer/biofilm; Anaerobic; Membrane